2018
DOI: 10.1111/evo.13459
|View full text |Cite
|
Sign up to set email alerts
|

Irreproducible text-book “knowledge”: The effects of color bands on zebra finch fitness

Abstract: Many fields of science-including behavioral ecology-currently experience a heated debate about the extent to which publication bias against null findings results in a misrepresentative scientific literature. Here, we show a case of an extreme mismatch between strong positive support for an effect in the literature and a failure to detect this effect across multiple attempts at replication. For decades, researchers working with birds have individually marked their study species with colored leg bands. For the z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 94 publications
0
21
0
Order By: Relevance
“…An exhaustive review and meta-analysis on plumage coloration of blue tits ( Cyanistes caeruleus ) revealed that, after dozens of publications studying the function of plumage ornamentation in this species, the only robust conclusion is that females’ plumage differs from that of males ( Parker, 2013 ). Another example is the long-believed effect of leg bands of particular colours on the perceived attractiveness of male zebra finches ( Taeniopygia guttata ), which has been also experimentally and meta-analytically refuted ( Seguin and Forstmeier, 2012 ; Wang et al, 2018 ). Finally, the existence of a badge of status in a non-bird model species, the paper wasp ( Polistes dominulus ; Tibbetts and Dale, 2004 ) has also been challenged multiple times (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…An exhaustive review and meta-analysis on plumage coloration of blue tits ( Cyanistes caeruleus ) revealed that, after dozens of publications studying the function of plumage ornamentation in this species, the only robust conclusion is that females’ plumage differs from that of males ( Parker, 2013 ). Another example is the long-believed effect of leg bands of particular colours on the perceived attractiveness of male zebra finches ( Taeniopygia guttata ), which has been also experimentally and meta-analytically refuted ( Seguin and Forstmeier, 2012 ; Wang et al, 2018 ). Finally, the existence of a badge of status in a non-bird model species, the paper wasp ( Polistes dominulus ; Tibbetts and Dale, 2004 ) has also been challenged multiple times (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…An exhaustive review and meta-analysis on plumage coloration of blue tits (Cyanistes caeruleus) revealed that, after dozens of publications studying the function of plumage ornamentation in this species, the only robust conclusion is that females' plumage differs from that of males (Parker, 2013). Another example is the longbelieved effect of leg bands of particular colours on the perceived attractiveness of male zebra finches (Taeniopygia guttata), which has been also experimentally and meta-analytically refuted (Seguin & Forstmeier, 2012;Wang et al, 2018). Finally, the existence of a badge of status in a non-bird model species, the paper wasp (Polistes dominulus; Tibbetts & Dale 2004) has also been challenged multiple times (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…"S" means that the study element in the replication study is similar enough to the original study that it would be considered a fair test of the original hypothesis, and "D" means that the study element is distinctly different in original and replication studies, testing beyond the original hypothesis So far, there have been no equivalent, large-scale replication projects in ecology or related fields. However, meta-analytic studies have shown that several classic behavioral ecology findings do not reliably replicate (Sánchez-Tójar et al, 2018;Seguin & Forstmeier, 2012;Wang et al, 2018). In addition, all of the conditions expected to drive low rates of replication mentioned above appear common in ecology and evolution (Fidler et al, 2017;Parker et al, 2016): low power (Jennions & Moller, 2000), publication bias (Cassey, Ewen, Blackburn, & Moller, 2004;Fanelli, 2012;Franco et al, 2014;Jennions & Moller, 2002;Murtaugh, 2002), and prevalence of questionable research practices (Fraser et al, 2018).…”
Section: Cause For Concern Over Replication Ratesmentioning
confidence: 99%